Overexpression of endoplasmic reticulum stress-related proteins, XBP1s and GRP78, predicts poor prognosis in pulmonary adenocarcinoma. (August 2018) - Kwon, Dohee; Koh, Jaemoon; Kim, Sehui; Go, Heounjeong; Min, Hye Sook; Kim, Young A; Kim, Deog Kyeom; Jeon, Yoon Kyung; Chung, Doo Hyun
Highlights: ER stress-related molecules, GRP78 and XBP1s, are variably expressed in lung cancer. GRP78 and XBP1s levels are related to histologic and genetic status of lung cancer. XBP1s and GRP78 expression have prognostic implication in adenocarcinoma of the lung. ER stress pathway may be a potential therapeutic target in lung cancer. Abstract: Objectives: Endoplasmic reticulum (ER) stress is associated with tumor development and progression via pro-tumorigenic and anti-tumorigenic effects. However, the clinicopathological implications of the ER stress pathway in non-small cell lung cancer remain unclear. Therefore, we sought to address these issues in this study. Materials and methods: Expression of two ER stress-related proteins, GRP78 and XBP1 spliced-form (XBP1s), was evaluated in pulmonary adenocarcinoma (pADC; n = 369) and squamous cell carcinoma (pSqCC; n = 246) using immunohistochemistry. Results: Expression levels of GRP78 and XBP1s were significantly higher in pADCs and pSqCCs, respectively (both, P < 0.0001). In the pADC group, XBP1s expression was higher in patients with ALK translocation than in those with wild-type ALK, wild-type EGFR, or EGFR mutation ( P < 0.005). No significant difference in GRP78 expression according to ALK or EGFR status was noted. pADC harboring high GRP78 expression exhibited an increased XBP1s expression ( P = 0.0067). Higher XBP1s expression was associated with shorter disease-free survival (DFS) in patients with pADC ( P = 0.026) and in those with ALK translocation ( P = 0.001). Higher GRP78 expression was associated with shorter DFS in patients with pADC ( P = 0.029) and those with EGFR mutation ( P = 0.005). Multivariate survival analysis revealed that high XBP1s expression was an independent predictor of poor DFS in pADC ( P = 0.004, hazard ratio [HR] = 3.115), and that high GRP78 expression was an independent predictor of poor DFS in EGFR -mutated pADC ( P = 0.007, HR = 2.168). Taken together, high expression of XBP1s or GRP78 was an independent poor prognostic factor in pADC ( P = 0.002, HR = 2.403). Conclusion: GRP78 and XBP1s are expressed variably in pADC, but their overexpression is associated with poor patient prognosis. The ER stress pathway may be a prognostic biomarker and potential therapeutic target for pADC.